Sexualidade e gênero segundo educadoras de ciências e biologia: limites, resistências e possibilidades da educação sexual na escola - Lourenço, Silmara Silveira (Universidade Federal de São Carlos, 2019)
Sexual education in schools is usually based only on a biological and technicist bias, which leads to universalizing and essentialising visions about sexuality and gender. For this research were interviewed the educators of the disciplines of Sciences and Biology of public schools of Sorocaba - SP, considering that these professionals are considered the holders of the discourse authorized for curricular contents about the body. However, these are issues that also encompass social, historical and cultural points of view. The research has a qualitative character and from semi-structured interviews, using the concepts of discursive practices in Bakhtinian conceptions, we seek to understand the different discourses of the subjects of the research on sexuality and gender in the teaching of sciences and biology, understanding that such discourses are not individual but collective; socially constructed. We seek to identify in which theoretical-methodological perspectives educators guide their pedagogical practices and which approaches they consider pertinent for the teaching of sex education in their disciplines. We observe that there are several devices that act on sexual education, among them, religious and moral values and beliefs about sexuality and gender are significant. The values that the school management and students possess work as a coping to be addressed by some education professionals. Also, the absence of training was pointed out in the interviews, mainly in relation to sex education in addition to the medical-biological discourse, which causes anguish those interviewees who feel the need for a more plural approach. Therefore, in the midst of such difficulties, we perceive strategies and actions built by the educators for dialogical approaches, project realizations and activities that consider the theme in a broad and democratic way.
Sexuality and gender according to educators of science and biology: limits, resistances and possibilities of sex education in school
Keywords: Sexualidade; Gênero; Educação Sexual; Ciências e Biologia; Práticas discursivas; Sex Education; Sexuality; Gender; Science and Biology education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO